Symbiotic effects of high-pressure acid etching on the oxidation characteristics of coal during coal-and-gas co-mining - Lin Li; Xinyi Chen; Xiangjun Chen; Jishan Liu; Jie Zeng; Chao Pan; Furu Kang; Junwei Yuan; Yunfei Du (Fuel, 2027)

Experimental validation and surrogate-assisted evolutionary optimization on polyline-based core sandwich structures - Xintong Wu; Guanguan Sun; Zan Yang; Yuhang Chen; Lin Zhu; Junwei Long; Haobo Qiu (Engineering Structures, 2026)

Reducing carbon mineralization and enhancing carbon storage in coastal earth aquaculture pond sediment using Spartina alterniflora-derived biochar - Ping Yang; Junwei Wang; Yongxin Lin; Hong Yang; Wenjing Liu; Qian Zhu; Chuan Tong; Dongyao Sun; Linhai Zhang; Kam W. Tang (Agriculture, Ecosystems & Environment, 2026)

BcSak1-mediated adaption to low temperature in Botrytis cinerea represents optional targets for management of cold-tolerant diseases on harvested fruits - Ziwei Su; Yuxuan Lin; Xinyi Long; Jiaxi Zhang; Yin Li; Chuanxi Zhu; Wenjin Yan; Congcong Wang; Yiwen Wang; Junwei Zhao; Xiang Li; Aruppillai Suthaparan; et al. (Postharvest Biology and Technology, 2026)

Effect of size-dependent mixed-wettability on pore-scale immiscible displacement dynamics: A numerical study - Yusong Xu; Bo Shui; Zidi Lin; Li’ao Su; Zhaolin Gu; Junwei Su (Advances in Water Resources, 2026)

Turning ecological nuisance to environmental resource: Use of Spartina alterniflora-derived biochar to decrease N2O production potential and emission in coastal aquaculture pond sediment - Wenjing Tan; Kaiyuan Liu; Ping Yang; Kam W. Tang; Hong Yang; Chuan Tong; Wenjing Liu; Dongyao Sun; Junwei Wang; Yongxin Lin; Yifei Zhang (Journal of Environmental Chemical Engineering, 2026)

The luxury effect under environmental filtering: Drivers of residential plant diversity in 15 high-altitude cities - Yao Yao; Zhiwen Gao; Lin He; Luyi Lan; Xiaoya Yu; Ruishen Yang; Junwei Wang; Yuandong Hu; Qiong La; Liangjun Da (Journal of Environmental Management, 2026)

Trophic state regulates nitrous oxide (N2O) emissions and associated indirect emission factors in coastal creeks - Qian Zhu; Ziyuan Chen; Ping Yang; Hong Yang; Wenjing Liu; Junwei Wang; Chuan Tong; Jujuan Gao; Dongyao Sun; Yongxin Lin; Kam W. Tang (Global and Planetary Change, 2026)

Layer-by-layer assembly of polycationic electrolytes onto cation exchange membranes for enhanced Li+/Mg2+ selectivity: A comparative study of polyethyleneimine and chitosan - Jiadi Ying; Zhen Cui; Xiaoxiang Xi; Junwei Zhu; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Yaochun Chen; Minfeng Zeng; et al. (Desalination, 2026)

Thermal threshold triggers hepatic immune reprogramming and oxidative exhaustion in large yellow croaker Larimichthys crocea - Caoqun Zheng; Rabia Zeb; Ronghui Zheng; Chao Fang; Junwei You; Kun Liu; Heshan Lin; Jun Bo (Marine Environmental Research, 2026)

Persistent soil resistome expansion following bacterial inoculation despite successful antibiotic bioremediation - Qilu Cheng; Mengjie Zhang; Biao Tang; Yuyi Yang; Eulyn Pagaling; Hans-Peter Grossart; Zulin Zhang; Dong Zhu; Junwei Ma; Hui Lin (Journal of Hazardous Materials, 2026)

Mechanochemical biochar enables electron-transfer-mediated ferrate(VI) activation for enhanced micropollutant degradation - Yufei Shi; Anting Ding; Yuhang Lin; Chengyu Zeng; Miao Jiang; Fuyu Xie; Hui Lin; Junwei Ma; Yongzhen Ding; Shangfeng Yang; Zulin Zhang (Environmental Research, 2026)

Genome-wide identification of the MYB transcription factor family of blackcurrant and the key role of RnMYB44 gene in drought tolerance - Lin Wang; Xuelin Zhang; Xueying Zhao; Hongyinga Li; Jiacheng Liu; Yu Zheng; Zongya Xing; Huixin Gang; Junwei Huo; Dong Qin (Planta, 2026)

Mechanistic insights into the role of nitrogen configurations driving efficient activation of low-dose ferrate (VI) for sulfonamides elimination - Zhikang Deng; Jinyao Zhu; Xi Chen; Minghui Xiang; Hui Lin; Junwei Ma; Song Cui; Zulin Zhang (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “YOLOv8-MDN-tiny: A lightweight model for multi-scale disease detection of postharvest golden passion fruit” [Postharvest Biol. Technol. 219 (2025) 113281] - Dengjie Chen; Fan Lin; Caihua Lu; JunWei Zhuang; Hongjie Su; Dehui Zhang; Jincheng He (Postharvest Biology and Technology, 2026)

Red phosphorus triggers endogenous iron activation of sludge biochar for peroxymonosulfate activation: Unravelling superoxide radical and non-radical degradation mechanisms - Minghui Xiang; Zhikang Deng; Yongfei Ma; Yifan Liu; Xiaoyu Xiang; Han Ding; Ranran Zhang; Hui Lin; Junwei Ma; Yongzhen Ding; Zulin Zhang (Journal of Environmental Chemical Engineering, 2026)

Fermented red quinoa (FRQ) effectively mitigates chronic alcohol-induced cognitive impairment and hepatic steatosis through multi-mechanistic pathways - Zi-Han Lin; Zhaohui Wang; FenFen Wei; Xinyao Zhu; Junwei Ma; Yan Wu; Song-Mei Chen; Li-Hua Song (Food Research International, 2026)

Integration of physiomics, transcriptomics and metabolomics to study the detoxification mechanism of blue honeysuckle under cadmium stress - Weixia Zhang; Xuelin Zhang; Kexin Liu; Xueying Zhao; Ruiqun Ma; Lin Wang; Peng Zhang; Junwei Huo; Dong Qin (Plant and Soil, 2026)

Decadal decline of the meridional overturning circulation in the eastern subpolar North Atlantic diagnosed from a high-resolution reanalysis dataset - Hanshi Wang; Xiaopei Lin; Jian Shi; Zhenhui Yi; Xingyue Xia; Junwei Chai (Ocean Dynamics, 2026)

Hot-Spot-Guided Generative Deep Learning for Drug-Like PPI Inhibitor Design - Heqi Sun; Jiayi Li; Yufang Zhang; Shenggeng Lin; Junwei Chen; Hong Tan; Ruixuan Wang; Xueying Mao; Jianwei Zhao; Rongpei Li; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Evolution pathway of heavy metal speciation during ultrasonic carbonation and subsequent cementitious utilization of MSWI fly ash - Jie Chen; Lianghui Li; Zhiliang Chen; Junwei Liu; Xiaoqing Lin; Xinyue Wang (Process Safety and Environmental Protection, 2026)

MoB2 nanozyme-decorated borate hydrogels with ROS-scavenging and antibacterial abilities for infected diabetic wound healing - Yueguang Fang; Chenxi Li; Ruifang He; Lanling Xiu; Dingwen Xiao; Miao Wang; Yuesheng Dong; Lin Sun; Junwei Ye (Chemical Engineering Journal, 2026)

Nanoscale zero-valent iron mediates Fe speciation-microbe synergism for simultaneous remediation of 2,3′,4,4′,5-pentachlorobiphenyl and Cd co-contaminated soil and safe rice production - Yangzhi Liu; Jinchuan Ma; Chenghu Yang; Jing Zhang; Honghui Wang; Qilu Cheng; Yingxia Liu; Qiang Wang; Hui Lin; Junwei Ma (Journal of Hazardous Materials, 2026)

Dynamic hyphal specialization remodeling enables Botrytis cinerea to overcome diverse host defenses during infection - Chen Qian; Yuxuan Lin; Chuanxi Zhu; Huan Liu; Junwei Zhao; Xiang Li; Dandan Ren; Jufen Li; Yiwen Wang; Ling Xu; Pinkuan Zhu (Physiological and Molecular Plant Pathology, 2025)

Thermal sensation and comfort models for non-uniform and transient environments, Part V: Enhancements of whole-body sensation model - Junwei Lin; Yan Liang; Junran Yang; Yongxin Xie; Hui Zhang; Jianlei Niu (Building and Environment, 2025)

Interfacial depassivation enables long-cycling silicon-based solid-state batteries without stack pressure - Lu Zhao; Junwei Han; Xin Qin; Qian Xu; Fei Yang; Junshu Sun; Pengcheng Dai; Lin Shi; Debin Kong; Linjie Zhi (Chemical Engineering Journal, 2025)

Insights into soil carbon metabolism and carbon sequestration capacity under organic fertilizer substitution model - Zirui Zhou; Yan Liao; Qian Zhang; Zicong Xiong; Junwei Tang; Jing Tian; Xiaolong Chang; Huailin Zhang; Junyu Xiang; Ziyuan Lin; Chaolan Zhang (Applied Soil Ecology, 2025)

Dual-functional tight ultrafiltration membrane constructed from aminoquinone networks for sufficient dye/salt selectivity and bacterial inactivation - Riri Liu; Hanna Vanermen; Jiale Du; Qin Chen; Zijian Yu; Junwei Li; Pengrui Jin; Junfeng Zheng; Alexander Volodin; Wenyuan Ye; Raf Dewil; Ming Xie; et al. (Desalination, 2025)

A novel method for local clothing insulation prediction to support sustainable building and urban design - Junwei Lin; Ying Jiang; Yongxin Xie; Jianlei Niu (International Journal of Biometeorology, 2025)
Clothing is crucial in thermal comfort evaluation, affecting heat exchange between the body and the environment. Assuming even clothing insulation across body segments can lead to inaccurate predictions, affecting building and urban design strategies. This study processed insulation data from 240 clothing ensembles to derive local insulation values. Regression models were developed to relate local and overall insulation values, allowing fast estimation of local insulation distribution for any given overall value. To validate the effectiveness of local clothing insulation values predicted by the proposed methods, measured real-time skin temperatures were collected from field experiments and compared with predicted values. Results demonstrated a significant accuracy improvement in the predicted local skin temperature from thermoregulation simulation combined with the proposed local clothing insulation estimation methods. The Jaccard Similarity Coefficient (JSC) increased by an average of 0.21, with body segments like the head, neck, shoulders, back, and arms showing nearly 0.4 or more improvement. These local insulation determination functions, used with a multi-nodal thermoregulation model, offer a simpler and more effective way to enhance thermal comfort assessment accuracy. By providing more precise local insulation values, these functions can help optimize building designs and urban planning strategies, leading to better thermal comfort for occupants.

Wave-induced sloping seabed residual response around a buried pipeline - Jie Lin; Yuan Gao; Yakun Guo; Junwei Liu; Lingyun Feng (Marine Georesources & Geotechnology, 2025)

Metformin alleviates cadmium-induced reproductive toxicity by enhancing mitochondrial biosynthesis and epigenetic modifications in female mice - Jiaqiao Zhu; Min Zhu; Hangbin Zhao; Yifan Lin; Xiaoxue Han; Ankai Tan; Yixian Wang; Yonggang Ma; Junwei Li; Zongping Liu (Toxicology and Applied Pharmacology, 2025)

Humic acid-supported nanoscale zero-valent iron for sustainable cadmium remediation and crop safety in farmland soil - Yangzhi Liu; Dongren Zhou; Peng Huang; Chenghu Yang; Jing Zhang; Honghui Wang; Qilu Cheng; Yingxia Liu; Chengxiang Gao; Jinchuan Ma; Hui Lin; Junwei Ma (Journal of Hazardous Materials, 2025)

Effects of semipermeable membrane-covered composting on greenhouse gas mitigation and microbiome at different ambient temperatures at an industrial scale - Junwei Yuan; Siyuan Lin; Yi Wang; Wenxiang He; Yangyang Li; Junda Wu; Liang Cai; Xiaoyan Kong; Dongqi You; Bo Liu; Jun Hou (Journal of Environmental Chemical Engineering, 2025)

Nonylphenol in agricultural soil system: sources, effects, fate, and bioremediation strategies - Qilu Cheng; Junwei Ma; Yuyi Yang; Hui Lin (Current Opinion in Environmental Science & Health, 2025)

Energy-saving and visual-thermal performance of multi-sectional DSF system in a typical office room across five climate zones in China - Feng Shi; Chenyuan Zheng; Junwei Lin; Xuan Yang; Yilin You; Mengsheng Yang; Xiaoqiang Hong (Building and Environment, 2025)

Uptake of plasmid reduces the adaptation of Shigella flexneri to disinfectants and increases transmission of antibiotic resistance genes - Xiaojun Lin; Ruiqi Han; Huishi Peng; Junwei Huang; Yanbin Xu; Qingxia Qiao; Lu Huang (International Biodeterioration & Biodegradation, 2025)

Interfacial engineered biomass-derived G/VMT-PCNCs networks as high-performance proton-conducting humidity sensors - Lirong Tang; Junwei Wu; Zhiyi Cao; Qiqi Hong; Fengcai Lin; Ningning Tan; Lan Zhao; Xinda You; Beili Lu; Xuan Yang; Biao Huang; Hanyang Liu (Carbohydrate Polymers, 2025)

Transitional behavior of calcareous sand with different clay contents - Hongyi Zhao; Yaru Gao; Fei Lin; Jinhai Zheng; Dong-Sheng Jeng; Shuang Han; Junwei Liu; Yifei Sun (Frontiers in Marine Science, 2025)
Calcareous sand with fines content was often encountered in offshore and onshore engineering. However, most previous research has primarily focused on the mechanical properties of clean calcareous sand. This study conducted a series of drained and undrained triaxial tests on calcareous sand-clay binary mixtures to investigate the impact of fines content on the strength and deformation characteristics of calcareous sand. The results indicate that specimens with varying fines content exhibit both strain hardening and softening behaviors under different confining pressures. With the addition of fines content from 0% to 10%, the extent of dilatancy decreases, resulting in a smaller peak friction angle compared to clean sand specimens. However, when fines content increases further to 25%, both the maximum dilatancy angle and peak friction angle show an increase. A similar trend is observed for the friction angle at the phase transition state (PTS). In the p ′ − q plane, the critical state line (CSL) remains constant despite changes in fines content, whereas in the e − p ′ 0 . 7 plane, the CSL shifts with variations in fines content. A unified CSL in the e − p ′ 0 . 7 plane can be obtained by applying the concept of equivalent skeleton void ratio. Additionally, the state dependence of the material is analyzed using both the modified state parameter and the state index. It was observed that the friction angles at both the PTS and the peak state (PS) are influenced by the state of the material, with the PTS friction angle showing a stronger correlation with the state index, while the PS friction angle is more closely linked to the state parameter.

YOLOv8-MDN-Tiny: A lightweight model for multi-scale disease detection of postharvest golden passion fruit - Dengjie Chen; Fan Lin; Caihua Lu; JunWei Zhuang; Hongjie Su; Dehui Zhang; Jincheng He (Postharvest Biology and Technology, 2025)

A case study of numerical simulation on the interaction among random waves, double caisson composite breakwater and seabed - Junwei Liu; Lin Cui; Yunping Jia; Honglei Sun (Ocean Engineering, 2025)

SILAR-assisted synthesis of Cu2O modified TiO2 nanotube arrays: Study on efficient photocatalytic dye degradation and hydrogen evolution - Junwei Hou; Lin Gan; Nan Bao; Chengye Zhang; Kailu Liu; Qingyao Wang (Journal of Water Process Engineering, 2024)

Subjective information in thermal comfort evaluation methods: A critical review - Yuxin Yang; Junmeng Lyu; Zhiwei Lian; Yongxin Xie; Ying Jiang; Junwei Lin; Jianlei Niu (Energy and Buildings, 2024)

Evaluating thermal sensation in outdoor environments - Different methods of coupling CFD and radiation modelling with a human body thermoregulation model - Dharmasastha K; Haobin Liang; Junwei Lin; Yongxin Xie; Yichen Yu; Jian-lei Niu (Building and Environment, 2024)

Effect of antibiotic perturbation on nitrous oxide emissions: An in-depth analysis - Wenjun Yu; Kashif Hayat; Junwei Ma; Xiaoping Fan; Yuyi Yang; Zulin Zhang; Qiaogang Yu; Mingrong Qian; Hui Lin (Critical Reviews in Environmental Science and Technology, 2024)

Lightweight network based on Fourth order Runge-Kutta scheme and Hybrid Attention Module for pig face recognition - Jianjun Guo; Yiyou Kong; Lijun Lin; Longqin Xu; Dachun Feng; Liang Cao; Jiexin Chen; Junwei Ye; Shuqing Ye; Zhaozhong Yao; Yue Liu; Tonglai Liu; et al. (Computers and Electronics in Agriculture, 2024)

Chemical characteristics, formation mechanisms, and geological evolution processes of high-salinity coal reservoir water in the Binchang area of the southern Ordos Basin, China - Yabing Lin; Shuangming Wang; Junwei Qiao; Hui Zhang; Ermeng Zhang; Yue Ma; Yutong Hao (International Journal of Coal Geology, 2024)

Building extra transport channels in mixed-matrix membrane for air dehumidification - Yingtian Xu; Junwei Xie; Runfeng Lin; Yuqi Zhu; Jiayi Wu; Rujing Hou; Runping Niu; Yichang Pan (Journal of Environmental Chemical Engineering, 2024)

Effect of nitro-substituted ending group on the photovoltaic and photocatalytic performance of non-fullerene acceptors - Jing Wang; Junwei Zhu; Chenxi Li; Yi Lin; Xiang Li; Hongyan Zhang; Zaifei Ma; Yan Lu (Chemical Engineering Journal, 2024)

Dictyosphaerium sp.-treated aerobic digestate of perishable waste as substitution for vegetable hydroponic nutrient solution - Mengjie Zhang; Xiaoyan Zhang; Qilu Cheng; Feifan Shi; Yuan Fu; Jianlin Xu; Bing Gu; Junwei Ma; Li Yang; Qifa Zhou; Hui Lin (Algal Research, 2024)

Differences of Pyrolysis Products and Controlling Factors of Oil-Rich Coal with Different Grain Sizes under Fully-Mechanized Mining Conditions - Junwei Qiao; Xiangyang Liang; Changjian Wang; Qingmin Shi; Lei Zhang; Longxiang Jiao; Gang Su; Yabin Lin; Weifeng Xue (Natural Resources Research, 2024)

Long-term biogas slurry application increases microbial necromass but not plant lignin contribution to soil organic carbon in paddy soils as regulated by fungal community - Zhaoming Chen; Jinchuan Ma; Junwei Ma; Jing Ye; Qiaogang Yu; Ping Zou; Wanchun Sun; Hui Lin; Feng Wang; Xinlin Zhao; Qiang Wang (Waste Management, 2024)

Unraveling how Fe-Mn modified biochar mitigates sulfamonomethoxine in soil water: The activated biodegradation and hydroxyl radicals formation - Yuying Wang; Haohao Lyu; Yuqian Du; Qilu Cheng; Yuxue Liu; Junwei Ma; Shengmao Yang; Hui Lin (Journal of Hazardous Materials, 2024)

Tapping the potential of anammox upgrading in full-scale wastewater treatment plants through biofilm-enhanced anammox and denitrification - Junwei Huang; Gang Wang; Ruizhi Dai; Jinsong Liao; Yuxin Li; Yiguo Hong; Jiapeng Wu; Qingxia Qiao; Jih-Gaw Lin; Yanbin Xu (Journal of Cleaner Production, 2024)

Numerical Analysis of Dynamic Response and Liquefaction Phenomena in Sandy Seabed Foundation around a Semi-Circular Breakwater under Wave Loading - Junwei Liu; Yunping Jia; Lin Cui; Honglei Sun; Xu Lv; Mohsen Saleh Asheghabadi (Journal of Marine Science and Engineering, 2023)
Understanding the stability of the seabed foundation holds paramount significance in guaranteeing the safety and structural soundness of the breakwater alongside additional offshore structures. This study aimed to investigate the stability of a sandy seabed foundation around a semi-circular breakwater under wave loading in nearshore areas. A coupled numerical model of waves, a semi-circular breakwater, and the seabed was developed based on the OpenFOAM platform. The VARANS equations were used to govern the wave behavior. Meanwhile, the Biot’s partially dynamic model was employed to numerically simulate the seabed response considering both consolidation under self-weight and dynamic response under wave loading. The effects of various wave parameters, seabed properties, and the radius of the structure on the dynamic response of the seabed and the depth of liquefaction were investigated. The numerical results indicate that an increase in wave height, period, and permeability coefficient intensifies the dynamic response of the seabed soil. Furthermore, an increase in water depth weakened the soil’s dynamic response. There was a negative correlation between the radius of the semi-circular breakwater and the dynamic response. The influence of Poisson’s ratio on the dynamic response of the seabed was relatively small. Furthermore, a stronger dynamic pore pressure response was observed at the connection between the semi-circular breakwater and the rubble foundation.

Regulation and role of extracellular polymeric substances in the defensive responses of Dictyosphaerium sp. to enrofloxacin stress - Qilu Cheng; Yangzhi Liu; Ligen Xu; Jing Ye; Qiang Wang; Hui Lin; Junwei Ma (Science of The Total Environment, 2023)

Causal relationships between chronotype and risk of multiple cancers by using longitudinal data and Mendelian randomization analysis - Shanshan Tian; Longtao Huangfu; Sizhi Ai; Junwei Zheng; Le Shi; Wei Yan; Ximei Zhu; Qianwen Wang; Jiahui Deng; Yanping Bao; Suhua Chang; Lin Lu (Science China Life Sciences, 2023)

Dynamic characteristics of heavy metal accumulation in agricultural soils after continuous organic fertilizer application: Field-scale monitoring - Wanchun Sun; Jing Ye; Hui Lin; Qiaogang Yu; Qiang Wang; Zhaoming Chen; Jinchuan Ma; Junwei Ma (Chemosphere, 2023)

Inhibition mechanism of α-glucosidase inhibitors screened from Tartary buckwheat and synergistic effect with acarbose - Lin Han; Huiqing Wang; Junwei Cao; Yunlong Li; Xiying Jin; Caian He; Min Wang (Food Chemistry, 2023)

Multiple genotypes infection and molecular characterization of Torque teno neovison virus: A novel Anelloviridae of mink in China - Weizhi Xin; Zhiyuan Guo; Lin Wang; Yifan Li; Haikun Shangguan; Kun Xue; Hongyan Chen; Hongliang Yang; Lili Zhao; Junwei Ge (Research in Veterinary Science, 2023)

Recent advances of seabed liquefaction around the vicinity of marine structures - Jie Lin; Dong-Sheng Jeng; Hongyi Zhao; Yuan Gao; Junwei Liu; Yakun Guo (Ocean Engineering, 2023)

Biodegradation of sulfametoxydiazine by Alcaligenes aquatillis FA: Performance, degradation pathways, and mechanisms - Yuqian Du; Qilu Cheng; Mingrong Qian; Yangzhi Liu; Feng Wang; Junwei Ma; Xin Zhang; Hui Lin (Journal of Hazardous Materials, 2023)

Dynamic damage characteristics of mudstone around hammer driven pile and evaluation of pile bearing capacity - Jichao Yin; Xiaoyu Bai; Nan Yan; Songkui Sang; Lin Cui; Junwei Liu; Mingyi Zhang (Soil Dynamics and Earthquake Engineering, 2023)

Experimental study on penetration characteristics of an open-ended pile under static and dynamic driving methods - Jingxue Lu; Hongfeng Guang; Lin Cui; Junwei Liu; Cheng Wang; Subramani Anandha Kumar (Soil Dynamics and Earthquake Engineering, 2023)

In-situ synthesis of covalently-bonded SnS2/FeS2 heterostructures for high rate sodium storage - Hewen Dong; Xixi Wang; Jun Jiang; Wanying Lin; Enzuo Liu; Jianli Kang; Chunsheng Shi; Junwei Sha; Biao Chen; Liying Ma (Chemical Engineering Journal, 2023)

Encapsulating selenium into mesoporous carbon for high-performance aqueous Cu-Se battery - Zhouxiang Wu; Xia Lin; Junwei Zhang; Xiquan Chu; Jiaxi Xu; Jing Li; Yiwen Liu; Haoxiang Yu; Lei Yan; Liyuan Zhang; Jie Shu (Chemical Engineering Journal, 2023)

Differential responses of soil nirS- and nirK-type denitrifying microbial communities to long-term application of biogas slurry in a paddy soil - Zhaoming Chen; Jinchuan Ma; Yinxiu Liu; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Qiang Wang (Applied Soil Ecology, 2023)

Study on damage constitutive relationship of mudstone affected by dynamic pile driving - Yamei Zhang; Jichao Yin; Xiaoyu Bai; Lin Cui; Songkui Sang; Junwei Liu; Nan Yan; Mingyi Zhang (Soil Dynamics and Earthquake Engineering, 2023)

Deformation and adjustment mechanism of segment joint in shield tunneling - Zhang Junwei; Guo Sicen; Lin Yun; Li Xue (Arabian Journal of Geosciences, 2023)

Fate of heavy metals and bacterial community composition following biogas slurry application in a single rice cropping system - Qiang Wang; Zhaoming Chen; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Jinchuan Ma (Journal of Soils and Sediments, 2022)

A 168-year temperature recording based on tree rings and latitude differences in temperature changes in northeast China - Yangao Jiang; Yuting Cao; Junhui Zhang; Zhuo Li; Guoqiang Shi; Shijie Han; Cassius E. O. Coombs; Chuan Liu; Xiaoguang Wang; Junwei Wang; Lin Hao; Qi Xu; et al. (International Journal of Biometeorology, 2021)

Effect of Quicklime on Microbial Community in Strong Acidic Soil - Junwei Liang; Xiangquan Yu; Yafan Cao; Jiguang Zhang; Ning Yan; Lin Xue; Xianjie Cai; Guoming Shen (Journal of Soil Science and Plant Nutrition, 2021)

Genetic changes and evolutionary analysis of canine circovirus - Lin Wang; Yifan li; Zhiyuan Guo; Ying Yi; Han Zhang; Haikun Shangguan; Chengshi Huang; Junwei Ge (Archives of Virology, 2021)

Mapping paddy rice using Landsat time series data in the Ganfu Plain irrigation system, Southern China, from 1988−2017 - Jingjing Cao; Xueliang Cai; Junwei Tan; Yuanlai Cui; Hengwang Xie; Fangping Liu; Lin Yang; Yufeng Luo (International Journal of Remote Sensing, 2021)

Influences of organic material application on the physically separated soil organic carbon and nitrogen fractions in rice fields - Qiaogang Yu; Jing Ye; Wanchun Sun; Hui Lin; Qiang Wang; Junwei Ma (Journal of Soils and Sediments, 2021)

Tree ring width‐based January–March mean minimum temperature reconstruction from Larix gmelinii in the Greater Khingan Mountains, China since AD 1765 - Yangao Jiang; Chuan Liu; Junhui Zhang; Shijie Han; Cassius E. O. Coombs; Xiaoguang Wang; Junwei Wang; Lin Hao; Shengzhong Dong (International Journal of Climatology, 2021)
A ring‐width chronology of Larix gmelinii (LG) was developed in the northern Greater Khingan Mountains region of China. The response function analyses revealed that the local mean minimum temperature of January–March ( T 1–3 ) was the most limiting factor affecting the radial growth of LG trees. Based on correlation analysis, a reconstructed T 1–3 series from 1765 to 2013 was produced using standard ring‐width chronology. The reconstruction explained 41.2% of the total variance in recorded monthly mean minimum temperatures from 1960 to 2013. The reconstructed T 1–3 series had similar variability when compared with the May–September mean temperature reconstruction in Inner Mongolia (IM) and the February–March mean minimum temperature reconstruction in Yichun (YC). This reconstructed T 1–3 series also captured the severe snow disaster and cold wave events recorded from historical documents in Heilongjiang and Inner Mongolia. Spatial correlations between reconstructed series and gridded temperature data also provided a high level of confidence. In addition, significant relationships between the reconstructed T 1–3 series and the Pacific Decadal Oscillation (PDO), El Niño–Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), solar activity, indicated that the T 1–3 variation might be influenced by large‐scale ocean–atmosphere interactions.

Simulation of oyster ecological carrying capacity in Sanggou Bay in the ecosystem context - Yaping Gao; Jianguang Fang; Fan Lin; Fengxue Li; Wenhao Li; Xiaoqin Wang; Meirong Du; Jinghui Fang; Weiwei Jiang; Hui Liu; Yitao Zhang; Junwei Wang; et al. (Aquaculture International, 2020)

Metal(loid) bioaccessibility and children’s health risk assessment of soil and indoor dust from rural and urban school and residential areas - Junwei Ma; Yuqian Li; Yanzhong Liu; Xunrui Wang; Chunye Lin; Hongguang Cheng (Environmental Geochemistry and Health, 2020)

Soil microbial activity and community composition as influenced by application of pig biogas slurry in paddy field in southeast China - Zhaoming Chen; Qiang Wang; Junwei Ma; Stephen Chapman; Ping Zou; Jing Ye; Qiaogang Yu; Wanchun Sun; Hui Lin; Lina Jiang (Paddy and Water Environment, 2020)

Identification of a GntR family regulator BusRTha and its regulatory mechanism in the glycine betaine ABC transport system of Tetragenococcus halophilus - Jieting Lin; Yunfei Zhu; Hanlan Tang; Junwei Yan; Lixin Luo (Extremophiles, 2019)

Influences of Nitrification Inhibitor 3,4-Dimethylpyrazole Phosphate on Heavy Metals and Inorganic Nitrogen Transformation in the Rice Field Surface Water - Qiaogang Yu; Junwei Ma; Wanchun Sun; Hui Lin; Qiang Wang; Jianrong Fu (Water, Air, & Soil Pollution, 2017)

Geological characteristics and main controlling factors of Permian lacustrine tight oil in the eastern part of the Junggar Basin - Junwei Zhao; Huaimin Xu; Cui He; Lin Li; Zhen Yi; Huijing Fang; Zhicheng Lei (Geosciences Journal, 2017)

Effect of di-n-butyl phthalate (DBP) on the fruit quality of cucumber and the health risk - Lei Wang; Xin Sun; Qin Chang; Yue Tao; Lihua Wang; Junwei Dong; Yulong Lin; Ying Zhang (Environmental Science and Pollution Research, 2016)

Effects of combined application of organic and inorganic fertilizers plus nitrification inhibitor DMPP on nitrogen runoff loss in vegetable soils - Qiaogang Yu; Junwei Ma; Ping Zou; Hui Lin; Wanchun Sun; Jianzhen Yin; Jianrong Fu (Environmental Science and Pollution Research, 2015)

Influence of TLR4 rs1927907 locus polymorphisms on tacrolimus pharmacokinetics in the early stage after liver transplantation - Zhaowen Wang; Shaohan Wu; Dawei Chen; Feng Guo; Lin Zhong; Junwei Fan; Zhihai Peng (European Journal of Clinical Pharmacology, 2014)

Soil microbial systems respond differentially to tetracycline, sulfamonomethoxine, and ciprofloxacin entering soil under pot experimental conditions alone and in combination - Junwei Ma; Hui Lin; Wanchun Sun; Qiang Wang; Qiaogang Yu; Yuhua Zhao; Jianrong Fu (Environmental Science and Pollution Research, 2014)

Differential proteomic analysis of polyubiquitin-related proteins in chemical hybridization agent-induced wheat (Triticum aestivum L.) male sterility - Hongzhan Liu; Gaisheng Zhang; Wanwan Zhu; William K. K. Wu; Qingsong Ba; Lin Zhang; Longyu Zhang; Na Niu; Shoucai Ma; Junwei Wang (Acta Physiologiae Plantarum, 2014)